Rousseau : the Discourses and other early political writings - Rousseau, Jean-Jacques, 1712-1778; Gourevitch, Victor (Cambridge : Cambridge University Press, 2019)
A comprehensive and authoritative anthology of Rousseau's important early political writings in faithful English translations. This volume includes the Discourse on the Sciences and Arts and the Discourse on the Origin and the Foundations of Inequality among Men - the so-called First and Second Discourses - together with Rousseau's extensive Replies to critics of these Discourses; the Essay on the Origin of Languages; the Letter to Voltaire on Providence; as well as several minor but illuminating writings - the Discourse on Heroic Virtue and the essay Idea of the Method in the Composition of a Book. In these as well as in his later writings, Rousseau probes the very premises of modern thought. His influence was wide-reaching from the very first, and it has continued to grow since his death. The American and the French Revolutions were profoundly affected by his thought, as were Romanticism and Idealism. This new edition features up-to-date translations, an expanded introduction, and an extensive editorial apparatus designed to assist students at every level access these seminal texts.
Discourse on the sciences and arts or First discourse -- Discourse on the origin and foundations of inequality among men or Second discourse -- Rousseau's notes -- Letter to Voltaire -- Essay on the origin of languages -- Idea of the method in the composition of a book -- Discourse on the virtue a hero most needs or On heroic virtue.
Title from publisher's bibliographic system (viewed on 29 Jun 2020).
Keywords: elektronické knihy; electronic books; Political science -- Early works to 1800.